2019
DOI: 10.1016/j.fuproc.2019.106142
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective upgrading of biomass pyrolysis oil using activated dolomite as a basic catalyst

Abstract: This study deals with a continuous process on a calcined dolomite operating at atmospheric pressure and by co-feeding water for cost-effective upgrading of raw bio-oil at 400 ºC and 500 ºC. The distribution of carbon in the feed to the product fractions (gas and upgraded bio-oil) and to the dolomite (as CO2 captured and coke) was investigated with time on stream, as well as the evolution of the gas and the upgraded bio-oil composition. Acids and high-molecular weight phenols were completely removed from the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…During fast pyrolysis, the use of an additional catalyst could be in situ (catalyst mixed with the biomass prior to be pyrolyzed) or ex situ (separating the catalyst and biomass by physical barriers) 62 . Catalysts, in general, are used to upgrade the bio‐oil quality by reducing the acidity of the liquid phase 84 . The fast pyrolysis of white and red oak particles, in the presence and absence of a catalyst, was done to evaluate its effect on the aqueous phase.…”
Section: Effect Of Different Pyrolysis Parameters On Acetic Acid Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…During fast pyrolysis, the use of an additional catalyst could be in situ (catalyst mixed with the biomass prior to be pyrolyzed) or ex situ (separating the catalyst and biomass by physical barriers) 62 . Catalysts, in general, are used to upgrade the bio‐oil quality by reducing the acidity of the liquid phase 84 . The fast pyrolysis of white and red oak particles, in the presence and absence of a catalyst, was done to evaluate its effect on the aqueous phase.…”
Section: Effect Of Different Pyrolysis Parameters On Acetic Acid Productionmentioning
confidence: 99%
“…62 Catalysts, in general, are used to upgrade the bio-oil quality by reducing the acidity of the liquid phase. 84 The fast pyrolysis of white and red oak particles, in the presence and absence of a catalyst, was done to evaluate its effect on the aqueous phase. It was found that the use of catalyst, ZSM-5, in-situ and ex-situ, decreased the acetic acid content of the aqueous phase.…”
Section: Catalytic Pyrolysismentioning
confidence: 99%
“…The alkaline catalyst will remove the protons on the carbon chain to form negative carbon ions, and then the β-bit breakage will occur to form small molecules of hydrocarbons such as styrene and other useful hydrocarbons. [90,91]…”
Section: Catalytic Cracking Mechanismmentioning
confidence: 99%
“…Steam reforming of bio‐oils can be performed in the presence of natural catalysts such as dolomite, olivine, limestone, calcite, magnesite, zeolites, and so on. These materials show good activities in steam reforming and can enhance the WGS reaction and the hydrogen selectivity . Furthermore, the natural catalysts are inexpensive and abundant and can be utilized directly or with some simple pretreatments .…”
Section: Catalysts For the Steam Reforming Of Bio‐oilsmentioning
confidence: 99%
“…However, compared with other catalysts, the calcined dolomite is deactivated more easily. Besides the carbon deposition, the calcined dolomite could be saturated by the carbonation of Ca(OH) 2 and CaO to CaCO 3 and lose the ability for CO 2 capture , .…”
Section: Catalysts For the Steam Reforming Of Bio‐oilsmentioning
confidence: 99%